What Do Viewers Talk About? Sentiment and Topic Analysis of Audience Comments on a Samsung Galaxy S26 Review on YouTube - Mufidatul Azmi; Ade Vidya Eryanti; Rika Kurniawati (Yayasan Literasi Sains Indonesia, 2026)
The rapid growth of digital media has positioned YouTube as a key platform for consumer information seeking, particularly through smartphone review content that shapes purchasing decisions. This study examines audience sentiment and identifies dominant discussion topics within comments on a YouTube review video of the Samsung Galaxy S26 Series. A quantitative descriptive approach was employed using text mining techniques, with data collected via web scraping yielding a dataset of 1,001 comments. The analysis comprised text preprocessing, lexicon-based sentiment analysis using the Indonesian Sentiment Lexicon (InSet), and topic modeling using Latent Dirichlet Allocation (LDA). The results indicate that positive sentiment dominates the discussion, accounting for 665 comments (66.4%), while 336 comments (33.6%) reflect negative sentiment. Positive comments cluster around themes of feature innovation, design appreciation, and favorable product evaluations, while also reflecting active audience engagement through content requests directed at the creator. Negative comments are primarily driven by concerns over screen reliability issues, particularly the green line problem associated with previous Samsung Galaxy devices. These findings highlight the value of YouTube comment analysis as a source of consumer intelligence, offering practical insights for digital marketing practitioners in managing brand perception and communication strategies during new product launch phases.